2018
DOI: 10.31101/jkk.544
|View full text |Cite
|
Sign up to set email alerts
|

Pengetahuan, sosial ekonomi, pola makan, pola haid, status gizi dan aktivitas fisik dengan kejadian anemia pada remaja putri

Abstract: Penelitian ini menggunakan desain penelitian kuantitatif, dengan menggunakan rancangan cross-sectional. Populasi pada penelitian ini adalah seluruh remaja putri kelas X di SMA Negeri 2 Pringsewu yang terdiri dari 159 remaja putri. Sampel pada penelitian ini adalah sampel total yang telah memenuhi kriteria inklusi dan eksklusi. Analisis data menggunakan uji chi square pada analisis bivariat dan regresi logistik ganda pada analisis multivariat. Berdasarkan hasil analisis bivariat didapatkan bahwa ada hubungan ya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
0
4
0
3
Order By: Relevance
“…9 As well as research conducted by Dzul (2018), students at SMA Negeri 2 Pringsewu, the value of p = 0.152 which means there is no relationship between physical activity and the incidence of anemia. 30 Research conducted by Renny and Ani (2017) also states that there is no relationship between physical activity and anemia, the results of the study obtained a value of p = 0.079, the study was conducted on female workers. 33 However, this study is not in line with Anis' research (2019), which was conducted on young women at senior high school, which stated that there is relationship betwen physical activity wit anemia with a p-value = 0.04.…”
Section: The Relationship Between Physical Activity and The Incidence Of Anemia In Adolescent Girls In Darussalam Islamic Boarding Schoolmentioning
confidence: 94%
See 1 more Smart Citation
“…9 As well as research conducted by Dzul (2018), students at SMA Negeri 2 Pringsewu, the value of p = 0.152 which means there is no relationship between physical activity and the incidence of anemia. 30 Research conducted by Renny and Ani (2017) also states that there is no relationship between physical activity and anemia, the results of the study obtained a value of p = 0.079, the study was conducted on female workers. 33 However, this study is not in line with Anis' research (2019), which was conducted on young women at senior high school, which stated that there is relationship betwen physical activity wit anemia with a p-value = 0.04.…”
Section: The Relationship Between Physical Activity and The Incidence Of Anemia In Adolescent Girls In Darussalam Islamic Boarding Schoolmentioning
confidence: 94%
“…Obtained pvalue = 0.003 so that it was found that there was a relationship between the pattern (frequency) of menstruation and the incidence of anemia. 30 According to Amaylia (2012), 3 things cause anemia, namely reduced red blood cell production (can be caused by lack of nutritional intake, bone marrow disorders, or disease), increased red blood cell destruction, and blood loss. 31 This study is also in line with Peni's research (2009) on female students at the Al-Hidayah Islamic Boarding School, Karangrayu District, the value of p = 0.007 which means there is a relationship between menstrual frequency and the incidence of anemia.…”
Section: The Relationship Between the Frequency Of Menstruation And The Incidence Of Anemia In Adolescent Girls At The Darussalam Islamicmentioning
confidence: 99%
“…Hal ini sejalan dengan hasil penelitian Hasyim (2018) yang menunjukan bahwa kejadian anemia pada remaja putri kemungkinan bukan hanya dampak dari rendahnya kualitas asupan gizi namun juga efek dari masalah ekonomi. Status ekonomi rendah berisiko terjadinya anemia dua kali dibandingkan dengan ekonomi tinggi pada remaja putri [19] . Di dalam penelitian ini juga melihat sumber pekerjaan orang tua sebagai latar belakang ekonomi keluarga.…”
Section: Pekerjaan Orang Tuaunclassified
“…Sikap merupakan suatu perilaku yang belum merupakan tindakan dan mempunyai tiga komponen yaitu: kepercayaan, ide, dan konsep suatu objek; kehidupan emosional atau evaluasi terhadap suatu objek; dan kecenderungan untuk bertindak (Wawan A dan Dewi M, 2011). Ekonomi orang tua dapat berdampak pada daya beli keluarga yang akan mempengaruhi asupan sehari-hari remaja putri yang kemudian akan menentukan status gizi remaja (Hasyim, 2018).…”
Section: Pendahuluanunclassified
“…Hasil penelitian menunjukkan bahwa subjek dengan anemia harnpir setengahnya status ekonomi rendah. Hal ini sesuai dengan pendapat Hasyim (2018) yaitu tingkat ekonomi rendah akan berpengaruh terhadap daya beli keluarga dan kemampuan dalam memilih makanan. Kondisi ini yang akan berpengaruh terhadap pemenuhan gizi pada remaja sehingga berisiko terjadi anemia.…”
Section: Kejadian Anemia Berdasarkan Tingkat Ekonomi Keluargaunclassified